Practical experience and strategies in periodic tapping - Ghani Mohd Noor A; Hai Teoh Cheng; Hashim Khairudin (Proceedings: Worshop on Exploitation Technologies to Addewss Current Labour Problems in the Rubber Industry, Kuala Lumpur, Malaysia, 5-6 December 1994.96-110.)
Shortage of rubber tappers in Golden Hope estates has become acute in the last five years with some estates experiencing shortage of 30 to 35;tappers. For this reason, four trials were set up using periodic tapping system(1/2 S d/2 2m/3 57;ET 2,5;8/y) on Sungei Mahang Estate in Nitai, New Rompin Estate in Bahau and Sungei Wangi Estate near Sitiawan on clones PB 217 and RRIM 600. The results from the trials on Sungei Mahang Estate indicated that the periodic tapping system gave yield per hectare over a five-year period ranging from 98 to 107;as compared to the control, tapped on 1/2 S d/2 86;conventional system. Mean yield per tapper ranged from 150;to 15-7;of the control. The trial on New Rompin Estate showed that yield was slightly depressed due to poor canopy. Mean yield per hectare over the five-year period ranged from 78 to 94;and the yield per tapper ranged from 118 to 132;as compared to the control conventional system. The New Rompin Estate trial indicated that there was a slight decrease in the mean annual girth increment for trees int he stimulated periodic tapping system as compared to the control. Mean annual girth increment for trees exploited on periodic system was 1.9 cm, while that of the control was 2.2 cm. However, the lower value on girth increment for the periodic system was mainly due to the lower girth increment contributed by Block C, situated on a low-lying soil, which had an initial poor tree tappability compared to Blocks A and B. Periodic-tapping system indicates that besides the reduction in the number of tappers required (33;), there are benefits such as comparable or better yield per hectare, higher yield per tapper and better bark reserve due to reduction in number of tapping. Thus, it is a good system for precocious high-yielding clones. Vesides young mature rubber, periodic tapping system can be used on prime-age trees on panels BO-2 and BI-1. It is, however, important to ensure effective stimulant application especially after the resting period, that is on groove if the lace is thick, and to provide adequate frequency.
Keywords: Periodic tappinp system